COMPARISON OF EFFECTIVENESS OF HAND WASHING WITH WATER, ANTISEPTIC SOAP, HAND SANITIZER GEL, AND ALCOHOL 70% AGAINST THE AMOUNT OF BACTERIA ON THE HANDS - Dhyana Ratmaja, I Gusti Agung Ngurah; Darwinata, Agus Eka; Pinatih, Komang Januartha Putra; Fatmawati, Ni Nengah Dwi (E-Jurnal Medika Udayana; Vol 12 No 8 (2023): E-Jurnal Medika Udayana, 2023)
Background: Hand washing is an activity that has to be achieved by everyone, by washing hands with excellent and correct techniques, able to make hands clean and of course can kill germs on the hands, good and proper hand washing can be done using soap and also running water or handwashing can also be done using alcohol or alcohol-based hand rubs. Methods: This research is an experimental study, One Group Pretest-posttest Design, taking primary data by taking samples from palms before and after washing using water, antiseptic soap, hand sanitizer gel, and alcohol 70%. Results: This study found that the effectiveness of washing hands with alcohol at 70% showed a decrease in bacterial number by 99%. In antiseptic soaps, there was a decrease in bacterial number by 86%. The use of hand sanitizer gel decreased bacterial number by 96%, and in water use, there was a decrease in bacterial number by 61%.  Conclusion: alcohol 70% has the most significant effect in decreasing the number of bacterial colonies among other hand washing materials.